1948
DOI: 10.1021/ja01182a502
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Dimethylamine to Benzoquinone

Abstract: Nord, el al.,1 condensed acetaldehyde with magnesium aluminum alkoxide catalysts ánd isolated from the reaction product the monoacetate of l, 3-butanediol. No mention is made in their papers of the ethyl ester of /3-hydroxybutyric acid which we have found to be present in the reaction mixture in approximately equimolecular proportion to the monoacetate of 1,3-butanediol. Similar proportions of the diol and the hydroxy acid have also been found in an oily by-product obtained in the commercial preparation of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1956
1956
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…When DMF was used as solvent, the reaction mixture, diluted with water, was extracted by methylene chloride, the organic layer washed by sodium hydroxide to remove phenols, and the solvent evaporated to give a red residue identified as 2,5-bisdimethylamino-p-benzoquinone (always in small amounts). It had a correct elemental analysis, melting point, and an UV spectrum in agreement both with literature data (Braude, 1945) and with a sample prepared by known methods (Baltzly and Lorz, 1948;Martynoff and Tsatsas, 1947). The NMR spectrum showed two singlets at <5 (ppm) 3.30 (methyl protons) and 5.45 (ring protons), with intensity ratio 6:1.…”
Section: Methodssupporting
confidence: 62%
“…When DMF was used as solvent, the reaction mixture, diluted with water, was extracted by methylene chloride, the organic layer washed by sodium hydroxide to remove phenols, and the solvent evaporated to give a red residue identified as 2,5-bisdimethylamino-p-benzoquinone (always in small amounts). It had a correct elemental analysis, melting point, and an UV spectrum in agreement both with literature data (Braude, 1945) and with a sample prepared by known methods (Baltzly and Lorz, 1948;Martynoff and Tsatsas, 1947). The NMR spectrum showed two singlets at <5 (ppm) 3.30 (methyl protons) and 5.45 (ring protons), with intensity ratio 6:1.…”
Section: Methodssupporting
confidence: 62%
“…Absolute Configuration of 11c and the Addition of Prolinol to it. ( S )-(+)-2-(Hydroxymethyl)pyrrolidine (“prolinol”) 20 combines with 11c as summarized in eq 8, giving in 82% yield a single structural isomer, shown below to be 15 . If 11c is racemic, it gives 15 as a mixture of diastereomers, which can be separated by chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…Amine nucleophiles can also be employed in the oxidation, substitution, and oxidation sequence. In 1948, it was determined the use of copper salts in the double addition of dimethylamine to benzoquinone allows for much higher reaction yields, because the starting quinone was no longer responsible for oxidizing the nucleophilic addition products . Further investigation of this method showed that the reaction was amenable to a number of dialkyl secondary amines (Scheme ) …”
Section: Reactions Of Phenols and Naphtholsmentioning
confidence: 99%